1991
DOI: 10.1001/archsurg.1991.01410290041008
|View full text |Cite
|
Sign up to set email alerts
|

Does the Retrocecal Position of the Vermiform Appendix Alter the Clinical Course of Acute Appendicitis?

Abstract: Ninety-four adult patients undergoing appendectomy for acute appendicitis were prospectively studied during a 2-year period. Patients were divided into retrocecal (group 1; n = 27 [29%]) and anterior (group 2; n = 67 [71%]) groups according to the position of the appendix. There was no statistical difference between the two groups in duration of symptoms, presenting signs and symptoms, and initial white blood cell count. Furthermore, retrocecal appendicitis was not associated with a higher rate of perforation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
1
11
1
1
Order By: Relevance
“…Some previous studies support the findings of the present study whereby the anterior position is more common 1,4,7 . Perhaps one could postulate that the frequency of the retrocaecal position varies among different ethnic groups 8–10 …”
Section: Discussionsupporting
confidence: 92%
“…Some previous studies support the findings of the present study whereby the anterior position is more common 1,4,7 . Perhaps one could postulate that the frequency of the retrocaecal position varies among different ethnic groups 8–10 …”
Section: Discussionsupporting
confidence: 92%
“…In beiden konnte kein signifikanter Zusammenhang zwischen der Lage der Appendix und der Perforations-bzw. Komplikationsrate bei Appendizitis gezeigt werden [4,10].…”
Section: Diskussionunclassified
“…8,[15][16][17] Clinical features typically do not differ between retrocecal (posterior to the cecum) and nonretrocecal appendicitis. 18,19 When the appendix is extraperitoneal (ie, posterior to the peritoneum with no peritoneal lining, unlike more cases which are intraperitoneal) and retrocecal, patients exhibit less abdominal pain, less focal abdominal tenderness, more back or flank pain, a longer duration of symptoms before diagnosis, and higher perforation rates. [18][19][20] Other appendiceal locations include subcecal (2%), anterior or preilial (1%), within a hernial sac (2%), right upper (4%), and left upper and lower quadrants (<0.1% each).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 When the appendix is extraperitoneal (ie, posterior to the peritoneum with no peritoneal lining, unlike more cases which are intraperitoneal) and retrocecal, patients exhibit less abdominal pain, less focal abdominal tenderness, more back or flank pain, a longer duration of symptoms before diagnosis, and higher perforation rates. [18][19][20] Other appendiceal locations include subcecal (2%), anterior or preilial (1%), within a hernial sac (2%), right upper (4%), and left upper and lower quadrants (<0.1% each). 8,17 Guidry SP et al have concluded that anatomic variations of the location of appendix are often responsible for delays in the diagnosis of appendicitis.…”
Section: Introductionmentioning
confidence: 99%